If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 9 = -6y + 15 Reorder the terms: 9 + -3y = -6y + 15 Reorder the terms: 9 + -3y = 15 + -6y Solving 9 + -3y = 15 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 9 + -3y + 6y = 15 + -6y + 6y Combine like terms: -3y + 6y = 3y 9 + 3y = 15 + -6y + 6y Combine like terms: -6y + 6y = 0 9 + 3y = 15 + 0 9 + 3y = 15 Add '-9' to each side of the equation. 9 + -9 + 3y = 15 + -9 Combine like terms: 9 + -9 = 0 0 + 3y = 15 + -9 3y = 15 + -9 Combine like terms: 15 + -9 = 6 3y = 6 Divide each side by '3'. y = 2 Simplifying y = 2
| 23-y=17 | | 14=-1+3x | | 18=5x-3(3x+7) | | 18x^2-31xy+6y^2= | | 8-8v+6=14-8v | | h(t)=-16t+28t+200 | | 3X-1ab=40 | | 9z*7z^4= | | 7r+3=38 | | -8b-4=6 | | h(t)=-16t*28t+200 | | z-8z=7z-3-z | | x+3+2x-6=13 | | f(x)=2x^2-11x+6 | | (2+2i)(3-i)= | | 5x+91-2x=140 | | 60000-3200= | | -6x-8x=-14 | | f(-1)=2x^2-11x+6 | | -3(b+4)-7b=-6b-(5b+2) | | 4n++6-2n=2(n+3) | | 5x+60=3x-40 | | 10x+13=1x+10 | | 700y+15=560y+50 | | f(x)=[[0.5x]] | | 6+5k=6 | | -19+3y+10=0 | | -9-15.6x=11.1x-22.95 | | 3(3x+4)=-2x-5-7x+20 | | F(x)=-2x-11x+6 | | 2v+7=4 | | 455=x+3x+1.5x+180 |